Pawn Mechanism Analysis at PT. Pegadaian (PERSERO) Mandailing Natal Sharia Service Unit - Ella Safitri; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
Pegadaian (Persero) Madina Syariah Service Unit carries out pawning with a purpose that is in accordance with the pawnshop’s mission, namely providing convenience to people who want to make transactions that are halal, providing superior returns for investors and PT. Pegadaian (Persero) Madina’s services have met the requirements in accordance with the legal umbrella of sharia pawnshops, but there are also customers who cancel their pawn financing because customers feel that the pawn items assessed are not in accordance with the customer’s wishes. The supporting factors for Madina sharia pawnshop customers to obtain pawn financing at PT Pegadaian (Persero) Madina Sharia Service Unit are the cooperation between Madina sharia pawnshops and customers both in fulfilling requirements, financing procedures and financing processes.